ChemInform Abstract: Tungsten Oxychloride Compounds Containing [W6O6Cl12]n‐ (n = 2, 3) Clusters. Issue 5 (4th February 2014) - Hummel, Thorsten; Glaser, Jochen; Stroebele, Markus; Meyer, H.‐Juergen
Abstract Compounds (III) and (V) are obtained by simple neutralization of aq.